Hepatic Hepcidin Gene Expression in Dogs with a Congenital Portosystemic Shunt - Frowde, P.E. (J Vet Intern Med, 2014)
BACKGROUND: Microcytic anemia is common in dogs with a congenital portosystemic shunt (cPSS) and typically resolves after surgical attenuation of the anomalous vessel. However, the pathophysiology of the microcytic anemia remains poorly understood. Hepcidin has been a key role in controlling iron transport in both humans and animals and in mediating anemia of inflammatory disease in humans. The role of hepcidin in the development of microcytic anemia in dogs with a cPSS has not been examined. HYPOTHESIS: To determine whether hepatic hepcidin mRNA expression decreases, while red blood cell count (RBC) and mean corpuscular volume (MCV) increase in dogs after surgical attenuation of a cPSS. ANIMALS: Eighteen client‐owned dogs with confirmed cPSS undergoing surgical attenuation. METHOD: Prospective study. Red blood cell count (RBC) and mean corpuscular volume (MCV), together with hepatic gene expression of hepcidin, were measured in dogs before and after partial attenuation of a cPSS. RESULTS: There was a significant increase in both RBC (median pre 6.17 × 10(12)/L, median post 7.08 × 10(12)/L, P < .001) and MCV (median pre 61.5fl, median post 65.5fl, P = .006) after partial surgical attenuation of the cPSS. Despite the increase in both measured red blood cell parameters, hepatic gene expression of hepcidin remained unchanged. CONCLUSIONS AND CLINICAL IMPORTANCE: This study found no evidence that dysregulated production of hepcidin was associated with anemia in dogs with a cPSS.